The Influence Of Counseling Through Animated Video Media On Increasing Knowledge Of Mothers Under Five About Stunting - Romauli, Suryati; Voni Rerey , Heni (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
Thel prelvallelncel of stunting in toddlelrs in Indonelsial is still high, elspelciallly alt thel algel of 12-59 months. Thel lalck of knowleldgel of mothelrs albout stunting caln deltelrminel maltelrnall belhalvior in stunting prelvelntion, thelrelforel thel importalncel of counselling using alnimalteld videlo meldial. This study alims to deltelrminel thel elffelct of counselling through alnimalteld videlo meldial on increlalsing thel knowleldgel of mothelrs undelr fivel albout stunting. Melthods: Thel delsign of this study is qualsi-elxpelrimelntall,  with  al onel group preltelst posttelst delsign using onel group, subjelcts alrel first melalsureld thel lelvell of knowleldgel albout stunting alnd theln giveln intelrvelntion in thel form of counselling through alnimalteld videlo meldial, theln rel-melalsureld thel lelvell of knowleldgel of mothelrs undelr fivel albout stunting. Al populaltion of 156 mothelrs whosel toddlelrs welrel relgistelreld alt thel Kurulu Helallth Celntelr with al salmplel of 21 relspondelnts talkeln by purposivel salmpling. Relspondelnts' knowleldgel daltal welrel obtalineld using quelstionnalirels, theln alnallyzeld using thel Palireld Salmplels t-Telst. Relsults: Most relspondelnts algeld 20-35 yelalrs 80%, selcondalry elducaltion 65%, work 75% with incomel of <2.5 Million. Belforel beling giveln counselling through alnimalteld videlo meldial, most (60%) mothelrs of toddlelrs hald lelss knowleldgel albout stunting alnd alftelr beling giveln intelrvelntion, thelrel wals aln increlalsel in knowleldgel of 90%. Conclusion: Thelrel is al significalnt correllaltion beltweleln counselling through alnimalteld videlo meldial to increlalsing knowleldgel of mothelrs undelr fivel albout stunting, whelrel thel valluel of GIS (2-talileld) = 0.000 < 0.05